MYC Participates In Lipopolysaccharide-Induced Sepsis Via Promoting Cell Proliferation And Inhibiting Apoptosis - Yin Li; Chengqi Kong; Lei Feng; Wenliang Tang; Mengwei Chen; Zhiyuan Zheng (Cell Journal, 2020)
Objective This study aimed to explore the potential mechanism of MYC proto-oncogene, BHLH Transcription Factor (MYC) gene, on sepsis.